Comparative Analysis of proposed Multilateral Investment Court and Permanent Multilateral Appellate Mechanism: Dilemma, Value, and Best Path Choice - Jillani, Muhammad Abid Hussain Shah; Hussain, Amjad; Mushtaq, Shahzada Aamir (The journal of contemporary issues in business and government, 2021)
The present study finds that establishing a permanent appeals mechanism is essential to resolve the current legitimacy crisis regarding investor-State dispute settlement. Currently, States have proposed two basic models of investment arbitration appellate reform to Working Group III of the UN Commission on International Trade Law, namely the formation of a Multilateral Investment Court (MIC) and a Permanent Multilateral Appellate Process(PMAP). The Latter is more legitimate and feasible than the MIC. The Appellate Mechanism’s (AM) review scope should include legal and procedural errors to guarantee that the AM’s error rectification function is completely accomplished. To improve the efficiency of arbitration, factual inaccuracies should be confined to apparent errors. Although stare decisis is not yet a general concept in international arbitration, PMAP can employ the de facto stare decisis evolved in WTO judicial practice to promote coherence and predictability of verdicts.